2019
DOI: 10.3390/ani10010047
|View full text |Cite
|
Sign up to set email alerts
|

Do Dairy Farming Systems Differ in Antimicrobial Use?

Abstract: The quantitative assessment of antimicrobial use (AMU) in food-producing animals contributes to the provision of essential information for developing relevant and effective policies to reduce use and to control antimicrobial resistance. Information on AMU is available mainly for intensive dairy farming systems and specialized high-yielding breeds. The aim of this study is to investigate AMU in different dairy farming systems by comparing the treatment incidence in mountain farms with specialized high-yield dai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…Management factors have gained a growing interest within the field of antibiotic resistance research, however, the herd size of livestock farms appears to be the most significant one causing many of the other factors such as biosecurity, number of animal suppliers, human traffic in the herd ect. Raasch et al, 2018;Sørensen et al, 2018;Xu et al, 2020;Zuliani et al, 2019). The results presented here suggest that there is a strong association between the levels of tetracycline resistance in slaughter pigs and the type of production.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…Management factors have gained a growing interest within the field of antibiotic resistance research, however, the herd size of livestock farms appears to be the most significant one causing many of the other factors such as biosecurity, number of animal suppliers, human traffic in the herd ect. Raasch et al, 2018;Sørensen et al, 2018;Xu et al, 2020;Zuliani et al, 2019). The results presented here suggest that there is a strong association between the levels of tetracycline resistance in slaughter pigs and the type of production.…”
Section: Discussionsupporting
confidence: 49%
“…The overall fit of the final model captured the trend of the data well, however, the variance of the prediction seemed to increase for higher values. The ( Raasch et al, 2018;Sørensen et al, 2018;Xu et al, 2020;Zuliani et al, 2019). The results presented here suggest that there is a strong association between the levels of tetracycline resistance in slaughter pigs and the type of production.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…The various metrics used to measure antibiotic use in different published studies make it challenging to make comparisons; however, the data suggest that the dairy farms participating in the present study have a relatively low level of antibiotic consumption. Smaller herd sizes, such as those included in this study, which allow for better individual animal observation and care, could be a potential reason for the lower antibiotic consumption observed (44). In addition, Austria has a relatively low level of agricultural intensification, a high proportion of organic farms (22%), and a high use of dual-purpose breeds (75% of the national herd) (45, 46) which might be less sensitive to bacteriological infections.…”
Section: Discussionmentioning
confidence: 99%
“…The difference between farming system types can also play a major role. Indeed, it has been recently shown [ 35 ] that mountain farms with smaller herd sizes, which provide cows with access to pasture and limit concentrates in the diet, use less HPCIA than specialized dairy farms from lowlands. Moreover, it has been widely reported that higher productivity (notably higher milk yield) can be associated with a higher incidence of metabolic disorders, such as mastitis, lameness and other production diseases [ 36 ], requiring prompt veterinary intervention.…”
Section: Discussionmentioning
confidence: 99%